General chemistry - Whitten, Kenneth W.; Davis, Raymond E.; Peck, Larry ([S.l.] : Cengage Learning, 1999)
This best-selling text is summarized by "classic text, modern presentation." Its emphasis on fundamental skills and concepts and clearly explained problem-solving strategies continues to be a strength. The revision builds on the highly praised style and applications to everyday life that have earned this text a reputation as the voice of authority in general chemistry.
Keywords: Chemistry,general chemistry